From volunteers to vital forces: The untapped power of barangay health workers in curbing HIV in the Philippines - De los Santos, Janet Alexis A. (Annals of Tropical Research, 2024)
The Philippines is currently facing an alarming rise in HIV cases, becoming one of the global hotspots, despite international trends showing a decline. One of the critical challenges is the lack of accessible health services, particularly in rural areas, where HIV hubs are scarce and concentrated only in cities. The country also struggles with a shortage of healthcare workers, especially in community health. While Barangay Health Workers (BHWs) are available and are trained volunteers within local communities, they remain underutilized in the government’s HIV response. Empowering and training BHWs could be key to bridging the health manpower gap, especially in underserved areas. By involving BHWs in grassroots-level health promotion, HIV awareness, and prevention strategies, the Philippines could significantly improve access to care and community resilience, especially in remote regions where traditional health workers are overwhelmed. This paper highlights the potential of BHWs to become pivotal in addressing the HIV crisis through adecentralized and community-based approach.